Independence and Fraud Detection: Influence on The Professionalism of Forensic Auditor - Sandari, Tries Ellia (Archives of Business Research, 2018)
This study aims to analyze the influence of this study aimed to analyze the influence of audit risk, and investigative audit techniques, on independence, fraud detection and forensic auditor professionalism in Indonesia. This study uses a survey method conducted for all forensic auditors in Indonesia with 200 forensic auditors who have handled fraud cases. The number of samples used was 116 respondents. Data analysis and hypothesis in this study use Structural Equation Modeling (SEM) with PLS 20.0 software. The results of this study indicate that twelve hypotheses were accepted. The significance of this hypothesis shows directly through audit risk, investigative audit techniques on independence, fraud detection and forensic auditor professionalism, so that the forensic auditor’s professionalism in detecting fraud will increase.